2017
DOI: 10.1002/ieam.1957
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the joint toxicity of co‐applied pesticides into the ecological risk assessment process

Abstract: Pesticides are frequently formulated as mixtures of active ingredients. Although traditionally ecological risk assessments (ERAs) have focused on individual active ingredients, there is an ongoing effort in many jurisdictions to more formally include assessment of mixtures. The overall goal of this project was to describe an approach for conducting ERA of jointly applied pesticides. We suggest that standard testing of formulation mixtures is not warranted due to the low probability of synergy occurring at a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 38 publications
0
33
0
1
Order By: Relevance
“…Toxicity to mixtures of insecticides and/or other pesticides in foliar tank mixes or seed‐treatment formulations can be assessed through the use of concentration– or response–addition models (National Research Council 2013). Synergistic effects that might considerably increase toxicity would not be captured by these models, but they are relatively rare (Cedergreen 2014; Belden and Brain 2018). Olaya‐Arenas et al (2020) did not find any synergistic effects on survival when they chronically exposed larvae to milkweed leaves that were treated with a mixture of clothianidin, 2 herbicides, and 3 fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…Toxicity to mixtures of insecticides and/or other pesticides in foliar tank mixes or seed‐treatment formulations can be assessed through the use of concentration– or response–addition models (National Research Council 2013). Synergistic effects that might considerably increase toxicity would not be captured by these models, but they are relatively rare (Cedergreen 2014; Belden and Brain 2018). Olaya‐Arenas et al (2020) did not find any synergistic effects on survival when they chronically exposed larvae to milkweed leaves that were treated with a mixture of clothianidin, 2 herbicides, and 3 fungicides.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because potency estimates (i.e., LC 50 values) are not biological constants (Casarett et al 2003). Recently, Belden and Brain (2018) concluded that difference between predicted and observed values that are less than five-fold are not indicative of a GTA interaction and this five-fold criterion is consistent with guidance from the European Food Protection Agency (EFSA) that considers a less than five-fold difference not indicative of a significant interaction (EFSA 2013). This five-fold criterion was re-emphasized in EFSA’s recent draft guidance on mixtures testing and assessment for microbial and biological pesticides (EFSA 2018).…”
Section: Resultsmentioning
confidence: 70%
“…As discussed, compared with the IA model, the CA model is, in general, more conservative, yet with similar overall accuracy in prediction . Therefore, for this assessment scheme, the well‐established CA model is considered as an appropriate model to characterize hazards for a conservative Tier‐1 assessment, even though the CA model is conceptually devoted to only similarly acting components in a mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Refinement options of effects for single active ingredients can also be used for mixtures, such as geometric mean calculation, species sensitivity distribution (SSD) analysis, consideration of co‐formulant toxicity, and higher tier ecosystem studies . PNEC and RQ values of individual active ingredients can be calculated separately with different uncertainty factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation